Trauma and Transmission: Echoes of the Missing Past in Dora Bruder - Judith Greenberg (Studies in 20th & 21st Century Literature, 2007)
This essay begins with the ethical imperative that Dora Bruder puts forward: to pay attention to the stories of the pain of others that had been ignored during the Holocaust. But Dora Bruder is also full of "missing pieces"—missing details in Dora's life story, missing elements in the narrator's relationship with his father, and the missing understanding that necessarily occurs in relation to "knowing" trauma and particularly, the Holocaust. The essay looks at those "missing pieces" both through insights in trauma theory and through the lens of 9/11, which introduced a new sense of the "missing" to this writer. It proposes that the narrator's condition or quest as haunted by the missing can be understood as an aspect of "postmemory," a term introduced by Marianne Hirsch to describe the transmission of traumatic memories across generations. The essay explores how the narrator can represent the "next generation" that inherits the trauma of its parents as a kind of "postmemory." In this sense, Dora Bruder captures our own predicament of being possessed by the responsibility to remember the pain of others and yet unable to adequately know that past.
Keywords: Dora Bruder; Holocaust; suffering; human suffering; trauma; knowing; missing pieces; 9/11; September 11; postmemory